Immigrants' Life Satisfaction in Intermarriages with Natives: A Family Life Course Perspective - Annegret Gawron; Sarah Carol (International Migration Review, 2022)
What role do intermarriages (i.e., interethnic marriages) play in immigrants' life satisfaction? Only a few studies have addressed this question. While intermarriages are associated with upward mobility for immigrants, they are more likely to get divorced than intramarriages (i.e., marriages among co-ethnics), which suggests either a positive or negative association between intermarriage and immigrants' life satisfaction. Drawing on data from the German Socio-Economic Panel (1984–2018), we estimate three-level hybrid models to investigate immigrants' life satisfaction in inter- compared to intramarriages across the family life course. After controlling for socioeconomic characteristics, we find that intermarried immigrants had lower life satisfaction, especially after the birth of their first child. This result suggests that the socialization of children might be a more contentious issue in intermarriages. Overall, these findings illustrate that marriage types and the life course should be considered in future studies on immigrants' life satisfaction and integration.
Keywords: 320; social integration; intermarriage; exogamy; life satisfaction; family life course